PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT GRIYA SUKSES BERSAMA TANGERANG SELATAN - Lili Sularmi; Veritia Veritia; Feb Amni Hayati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The purpose of this study was to determine the effect of motivation and work discipline on employee performance at PT. Griya Sukses with South Tangerang. The method used is a quantitative descriptive method. The sampling technique used was random sampling using a sample of 53 respondents. Data analysis uses regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The result of this study is that price perception has a positive and significant effect on employee performance with a regression value of 0.564 and a calculated t value (6.444 > 2.008). Work discipline has a positive and significant effect on employee performance with a regression value of 0.512 and a calculated t value (4.887 > 2.008). The influence of motivation and work discipline simultaneously has a positive and significant effect on employee performance with a correlation coefficient value obtained of 0.729, meaning that the independent variable with the dependent variable has a strong influence with a coefficient of determination or simultaneous influence of 53.1%. That is, a considerable advantage in getting strong performance will come from the marriage of high levels of drive and job discipline. Motivated people who practice strict work ethics are more likely to be proactive, take initiative, be dedicated to attaining their objectives, and endeavor to elevate the standard of their job. They are also more inclined to face difficulties head-on and conquer them with tenacity. As a result, they do better than those who lack sufficient work discipline or are less driven.